2010
DOI: 10.1308/003588410x12664192076214
|View full text |Cite
|
Sign up to set email alerts
|

Medicolegal claims following laparoscopic cholecystectomy in the UK and Ireland

Abstract: INTRODUCTION The causes and outcomes of medicolegal claims following laparoscopic cholecystectomy were evaluated. SUBJECTS AND METHODS A retrospective analysis of the experience of a consultant surgeon acting as an expert witness within the UK and Ireland (1990-2007). RESULTS A total of 151 claims were referred for an opinion. Sixty-three related to bile duct injuries and four followed major vascular injury. Bowel injury resulted in 17 claims. A postoperative biliary leak not associated with a bile duct injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 14 publications
1
23
0
1
Order By: Relevance
“…The patient and the family must be informed in detail following the operation. It is wise to discuss the referral of the patient to a specialized hepatobiliary unit (74). The perception of the patient and family of negligent behavior of the surgical team is usually more noteworthy than the injury itself.…”
Section: Medicolegal Issues A) What Are the Medicolegal Perspectives mentioning
confidence: 99%
“…The patient and the family must be informed in detail following the operation. It is wise to discuss the referral of the patient to a specialized hepatobiliary unit (74). The perception of the patient and family of negligent behavior of the surgical team is usually more noteworthy than the injury itself.…”
Section: Medicolegal Issues A) What Are the Medicolegal Perspectives mentioning
confidence: 99%
“…These rising figures and large settlements mean that routine IOC has been reported to be cost effective due to its early detection of BDI as discussed [56,61]. A recent study investigating medicolegal claims following laparoscopic cholecystectomy in the United Kingdom and Ireland concluded that BDI is ''almost indefensible'' [89]. This statement means that although the protective effects of IOC against BDI continue to be debated in the absence of definitive evidence, the undeniable fact that IOC does reduce the cost of litigation will likely gain increasing gravitas with time, culminating in health organizations instigating routine IOC during LC for economic reasons.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Apart from early postoperative complications, there is also a risk of long-term sequelae as strictures of the common bile duct and repeated attacks of cholangitis. In addition, such injuries represent a vast economic burden to the society (8) and also represent a high rate of medico-legal claims (9). the treatment of bile duct injuries has changed since the introduction of laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%